2022
DOI: 10.1002/jor.25333
|View full text |Cite
|
Sign up to set email alerts
|

Endplate abnormalities, Modic changes and their relationship to alignment parameters and surgical outcomes in the cervical spine

Abstract: Modic changes (MC) and endplate abnormalities (EA) have been shown to impact preoperative symptoms and outcomes following spinal surgery. However, little is known about how these phenotypes impact cervical alignment. This study aimed to evaluate the impact that these phenotypes have on preoperative, postoperative, and changes in cervical alignment in patients undergoing anterior cervical discectomy and fusion (ACDF). We performed a retrospective study of prospectively collected data of ACDF patients at a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The initial PubMed search identified 259 articles, after which the title and abstract screening identified 36 potentially relevant articles. Two were excluded due to an inadequate follow-up of less than one year [ 25 , 26 ], another two were excluded because of the risk of potentially identical patients [ 27 , 28 ], and one article’s full-text could not be obtained [ 29 ]. Thirty-one articles were identified after a full-text review.…”
Section: Resultsmentioning
confidence: 99%
“…The initial PubMed search identified 259 articles, after which the title and abstract screening identified 36 potentially relevant articles. Two were excluded due to an inadequate follow-up of less than one year [ 25 , 26 ], another two were excluded because of the risk of potentially identical patients [ 27 , 28 ], and one article’s full-text could not be obtained [ 29 ]. Thirty-one articles were identified after a full-text review.…”
Section: Resultsmentioning
confidence: 99%
“…52 However, several recent studies suggest that the combined Modic-endplate disruption phenotype results in significantly greater back and neck pain compared to Modic changes independently. 20,45,61 The literature on this phenotype remains extremely limited. However, the clinical impact of concomitant endplate defects and Modic changes may significantly impact patient presentation and serve as a prognostic factor for patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…11,[17][18][19] While the exact etiology of MCs remains unclear, several studies have linked these lesions to both back and neck pain. [20][21][22][23][24] These most frequently occur in the lumbar region. Studies evaluating cervical changes remain limited but have increased in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been relatively few studies on the relevance between Modic changes and structural abnormalities of the cervical endplate and clinical diseases. In recent years, studies by Harada et al [ 7 ] and Baker et al [ 8 ] revealed that cervical endplate abnormalities can affect the preoperative and postoperative cervical sequence parameters, aggravate postoperative pain following, and increase ASD and reoperation rates. Although the impact of endplate abnormalities on the mechanical stability of the cervical spine was not explored, these studies indicated the importance of the morphological stability of the cervical endplate.…”
Section: Introductionmentioning
confidence: 99%